1983
DOI: 10.1021/j100224a020
|View full text |Cite
|
Sign up to set email alerts
|

Actinometric determination of absolute fluorescence quantum yields

Abstract: The absolute fluorescence quantum yield of 9,10-diphenylanthracene in deaerated cyclohexane, the value of which has long been a matter of controversy, has been determined by use of a new method based on chemical actinometry. This technique avoids many of the intrinsic error sources of the other absolute methods. The sample's emission intensity is measured by almost completely surrounding the sample with an actinometer solution, and the excitation intensity is directly measured with the same type of actinometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
201
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(211 citation statements)
references
References 0 publications
10
201
0
Order By: Relevance
“…29 Linear aggression analysis was employed to determine the relative PL intensities of the sample and references solutions over the range of concentrations. The quantum yield of the water soluble CQDs were recorded using the following equation: where Φ is the quantum yield, m is the slope from the plot of integrated fluorescence intensity versus absorbance.…”
Section: Characterisationmentioning
confidence: 99%
“…29 Linear aggression analysis was employed to determine the relative PL intensities of the sample and references solutions over the range of concentrations. The quantum yield of the water soluble CQDs were recorded using the following equation: where Φ is the quantum yield, m is the slope from the plot of integrated fluorescence intensity versus absorbance.…”
Section: Characterisationmentioning
confidence: 99%
“…Importantly, bulk oxidation of the open form (e.g., 1oo 2+ ) does not lead to formation 25 of the ring-closed state (e.g., 1cc 2+ ). Reduction of 1oo 2+ and 2oo 2+ leads to a full recovery of the spectrum of the neutral forms 1oo and 2oo, respectively.…”
mentioning
confidence: 99%
“…7200 cm -1 ). 25 The frontier molecular orbital diagrams obtained from DFT calculations 19 suggested that upon closing of the dithienylethene rings the system can best be described as two closeddithienylethenesratherthananend-cappedsexithiophene. That is, the properties are not those of a sexithiophene but instead are those of a dithienylethene.…”
mentioning
confidence: 99%
“…This value is notably higher than the reported values for some anthracene-containing compounds, such as 0.47 of 2-tert-butyl-9,10-bis[4-(iminostilbenyl)phenyl]anthracene (Danel et al, 2002) and 0.44 of 9-phenyl-10-(4-triphenylamine)anthracene. (Hamai & Hirayama, 1983) www.intechopen.com As expected, DPAn-LPS has the good emission stability at high temperature with high fluorescence quantum efficient yield because intramolecular aggregation of chromophores is effectively prevented by the rigid ladder structure. Zhou et al ) prepared a novel blue-light emitting terphenyl-bridged ladder polysiloxane (TB-LPS) as shown in Scheme 9.…”
Section: Fluorescent Materialsmentioning
confidence: 97%